Plant secondary metabolites: a key driver of litter decomposition and soil nutrient cycling. (15th August 2016) - Chomel, Mathilde; Guittonny‐Larchevêque, Marie; Fernandez, Catherine; Gallet, Christiane; DesRochers, Annie; Paré, David; Jackson, Benjamin G.; Baldy, Virginie
Summary: A broad and diversified group of compounds, secondary metabolites, are known to govern species interactions in ecosystems. Recent studies have shown that secondary metabolites can also play a major role in ecosystem processes, such as plant succession or in the process of litter decomposition, by governing the interplay between plant matter and soil organisms. We reviewed the ecological role of the three main classes of secondary metabolites and the methodological challenges and novel avenues for their study. We highlight emerging general patterns of the impacts of secondary metabolites on decomposer communities and litter decomposition and argue for the consideration of secondary compounds as key drivers of soil functioning and ecosystem functioning. Synthesis . Gaining a greater understanding of plant–soil organisms relationships and underlying mechanisms, including the role of secondary metabolites, could improve our ability to understand ecosystem processes. We outline some promising directions for future research that would stimulate studies aiming to understand the interactions of secondary metabolites across a range of spatio‐temporal scales. Detailed mechanistic knowledge could help us to develop models for the process of litter decomposition and nutrient cycling in ecosystems and help us to predict future impacts of global changes on ecosystem functioning. Abstract : Plant secondary metabolites (PSM) have a major influence on litter decomposition principally through their impacts on the activity of soil organisms. In this review, we present examples of key studies where PSM underpin mechanisms driving variation in decomposition processes and nutrient cycling. We argue that studies covering interactions of PSM across a range of spatio‐temporal scales (organisms, communities and ecosystem) are needed to further understand their importance in ecosystems.